Rayleigh waves in a thermoelastic granular medium under initial stress - S. M. Ahmed (International Journal of Mathematics and Mathematical Sciences)
We study the effect of initial stress on the propagation of Rayleigh waves in a granular medium under incremental thermal stresses. We also obtain the frequency equation, in the form of a twelfth-order determinantal expression, which is in agreement with the corresponding classical results.